2005
DOI: 10.1007/s00418-005-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of versican during postnatal development of rat temporomandibular joint disc

Abstract: To analyze the growth-related changes in extracellular matrix components in temporomandibular joint (TMJ) discs, the expression and localization of the core protein of a large chondroitin sulphate proteoglycan, versican, in rat TMJ discs during postnatal development (2-32 weeks) were examined using Western blot analysis, real-time quantitative PCR and immunohistochemistry. Western blot analysis showed that rat TMJ discs predominantly expressed one isoform (V1) and the core protein sharply increased after birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…Details of the antibodies used and epitope retrieval steps required for detection are provided in table 1 and suppliers are provided below. Monoclonal antibody (Mab) 5-D-5 to versican G3 domain [1,30,48] was a gift from Dr Firoz Rahemtulla, University of Alabama, Birmingham, AL, USA. Mab A7L6, rat anti perlecan domain IV [14,15] and MAb CS-56 to native CS [23] were purchased from Abcam, Cambridge, UK.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the antibodies used and epitope retrieval steps required for detection are provided in table 1 and suppliers are provided below. Monoclonal antibody (Mab) 5-D-5 to versican G3 domain [1,30,48] was a gift from Dr Firoz Rahemtulla, University of Alabama, Birmingham, AL, USA. Mab A7L6, rat anti perlecan domain IV [14,15] and MAb CS-56 to native CS [23] were purchased from Abcam, Cambridge, UK.…”
Section: Methodsmentioning
confidence: 99%
“…Occlusion between upper and lower teeth is an important factor that regulates jaw movement (Matthews, 1975). Previous studies have suggested the involvement of occlusal forces in the development of the extracellular matrices in the articular disc of the temporomandibular joint (Toriya et al. 2006; Feng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Versican is a large chondroitin sulphate proteoglycan which is involved in ECM assembly, cell proliferation, cell survival, cell attachment, cell migration, and perhaps also the regulation of inXammatory and immunological reactions. Toriya et al (2006) studied the core protein of versican during the post-natal growth of the temporomandibular joint (TMJ) discs. They were able to demonstrate that growth-related changes and regional diVerences in the expression of versican in the TMJ discs of growing rats reXect changes in the biomechanical environment caused by the development of orofacial functions.…”
Section: Skeletal Muscle Cartilage and Ecmmentioning
confidence: 99%